A Survey on Various Approaches of Automatic Optical Inspection for PCB Defect Detection - Kumar, Mukesh; Kumar, Manjesh (International Journal of Computer Sciences and Engineering, 2019)
The Printed circuit board (PCB) is one of the crucial components of the electronics industry. An automated visual inspection system is required to provide a fast and quantitative assessment of PCB, since manual defect detection system is not efficient and time-consuming. Machine vision technology is an alternative to manual inspections and measurements with the help of high-resolution digital camera and image processing. This paper presents the various possible defects in PCB that can affect the working of electronic gadgets. Major defects are classified mainly under Fatal and Potential that can be detected mainly by any of the three approaches as Referential, Non-referential, and, Hybrid to find out defects present in PCB. After a comparative study of these methods, we have tried to find out the significantly fast and accurate method.